Plocabulin, a novel tubulin-binding agent, inhibits angiogenesis by modulation of microtubule dynamics in endothelial cells - Carlos M. Galmarini; Maud Martin; Benjamin Pierre Bouchet; María José Guillen-Navarro; Marta Martínez-Diez; Juan Fernando Martinez-Leal; Anna Akhmanova; Pablo Aviles (BMC Cancer, 2018)
Abstract Background Vascular supply of tumors is one of the main targets for cancer therapy. Here, we investigated if plocabulin (PM060184), a novel marine-derived microtubule-binding agent, presents antiangiogenic and vascular-disrupting activities. Methods The effects of plocabulin on microtubule network and dynamics were studied on HUVEC endothelial cells. We have also studied its effects on capillary tube structures formation or destabilization in three-dimensional collagen matrices. In vivo experiments were performed on different tumor cell lines. Results In vitro studies show that, at picomolar concentrations, plocabulin inhibits microtubule dynamics in endothelial cells. This subsequently disturbs the microtubule network inducing changes in endothelial cell morphology and causing the collapse of angiogenic vessels, or the suppression of the angiogenic process by inhibiting the migration and invasion abilities of endothelial cells. This rapid collapse of the endothelial tubular network in vitro occurs in a concentration-dependent manner and is observed at concentrations lower than that affecting cell survival. The in vitro findings were confirmed in tumor xenografts where plocabulin treatment induced a large reduction in vascular volume and induction of extensive necrosis in tumors, consistent with antivascular effects. Conclusions Altogether, these data suggest that an antivascular mechanism is contributing to the antitumor activities of plocabulin.